ROLE OF ULTRASOUND IN MECHANISMS OF ANODE-CATHODE INTERACTIONS DURING ELECTROSPARK ALLOYING - N. M. Chigrinova; S. I. Lovygin; V. E. Chigrinov (Наука и техника)
The paper reveals results of investigations on mass transfer kinetics and dynamics of coating formation while using integral electrospark alloying method with additional ultrasonic exposure at different stages of formation. Nowadays, a classical method for electrospark alloying with hard-alloy anodes and impulse AC voltage frequency on the vibration exciter coil from 20 to 1600 Hz has been mainly used for application of protective and strengthening coatings within permissible thickness and characteristics. The key aspect of ultrasonic exposure application (frequency 22–44 kHz) during electrospark alloying is the possibility to increase further thickness of coatings to be formed even after reaching a brittle fracture threshold of the coating material. Methodology of the executed research activity has been based on integrated studies (gravimetric, metallographic, X-ray diffraction and electron microscopic) of coatings which are to be formed through compositions produced while using method of high-energy hot compaction and a “refractory carbide (WC) and a binding material“ system in the form of alloy based on nickel from the series of “colmonoy” Ni – Ni3B system which is alloyed with additions of copper and silicon. The initial surface treatment within ultrasonic frequency range (22–44 kHz) contributes to a noticeable increase in the mass transfer rate, which is primarily determined by chemical composition and thermodynamic stability of anodes. It is due to surface activation in the process of its preliminary deformation at ultrasonic frequency which creates additional conditions for striking of a spark.The final ultrasonic treatment improves coating quality due to its additional forging that leads to an increase of its structure homogeneity and density.